The influence of specialised HIV/AIDS sites on first time clients' initiative to seek VCT services : a case of Nkumba University students, Uganda - Bucyana, Allan (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.